Mouse Mammary Tumor Virus-Like Nucleotide Sequences in Canine and Feline Mammary Tumors - Hsu, Wei-Li; Lin, Hsing-Yi; Chiou, Shyan-Song; Chang, Chao-Chin; Wang, Szu-Pong; Lin, Kuan-Hsun; Chulakasian, Songkhla; Wong, Min-Liang; Chang, Shih-Chieh (Journal of Clinical Microbiology, 2010)
Mouse mammary tumor virus (MMTV) has been speculated to be involved in human breast cancer. Companion animals, dogs, and cats with intimate human contacts may contribute to the transmission of MMTV between mouse and human. The aim of this study was to detect MMTV-like nucleotide sequences in canine and feline mammary tumors by nested PCR. Results showed that the presence of MMTV-like env and LTR sequences in canine malignant mammary tumors was 3.49% (3/86) and 18.60% (16/86), respectively. For feline malignant mammary tumors, the presence of both env and LTR sequences was found to be 22.22% (2/9). Nevertheless, the MMTV-like LTR and env sequences also were detected in normal mammary glands of dogs and cats. In comparisons of the MMTV-like DNA sequences of our findings to those of NIH 3T3 (MMTV-positive murine cell line) and human breast cancer cells, the sequence similarities ranged from 94 to 98%. Phylogenetic analysis revealed that intermixing among sequences identified from tissues of different hosts, i.e., mouse, dog, cat, and human, indicated the MMTV-like DNA existing in these hosts. Moreover, the env transcript was detected in 1 of the 19 MMTV-positive samples by reverse transcription-PCR. Taken together, our study provides evidence for the existence and expression of MMTV-like sequences in neoplastic and normal mammary glands of dogs and cats.